Coherent Light Microscopy Imaging and Quantitative Phase Analysis - Ferraro, Pietro; Wax, Adam.; Zalevsky, Zeev.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book deals with the latest achievements in the field of optical coherent microscopy. While many other books exist on microscopy and imaging, this book provides a unique resource dedicated solely to this subject. Similarly, many books describe applications of holography, interferometry and speckle to metrology but do not focus on their use for microscopy. The coherent light microscopy reference provided here does not focus on the experimental mechanics of such techniques but instead is meant to provide a users manual to illustrate the strengths and capabilities of developing techniques. The areas of application of this technique are in biomedicine, medicine, life sciences, nanotechnology and materials sciences.
Quantitative Phase Microscopy with Digital Holography Approach with High-Coherence Light Sources -- Quantitative Phase Microscopy with Digital Holography Approach with Low-Coherence Light Sources -- Digital Holographic Microscopy with Femtosecond Laser Sources for Characterization of Fast Dynamic Events and Process -- Quantitative Microscopy with a Photorefractive-Based Principle -- Application of Interference Microscopy in Microfluidics and Optofludics Systems -- Optofluidic-Based Microscope -- Characterization of Optical Microsystems Devices (Microlenses, Liquid Lenses, Integrated Optics Interferometrers, Waveguides, MEMs, MOEMs) -- Super-Resolution in Interference Microscopy -- Microscopy with UV Light Sources -- Microscopy with IR Sources -- 3D Imaging for Analysis and Tracking of Particles in Fluidodynamic Physics -- Visualization of Trapping Systems to Study Paths of Particles -- Optical Coherent Method for Evaluation and Recognition of Bio-Agents -- Special Methods with Fabrication and Characterization of Self-Assembled Structures. Phase Shifting Techniques in Microscopy.
Keywords: Physics; Radiology, Medical; Microscopy; Biomaterials; Nanotechnology; Surfaces (Physics).; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Biological Microscopy; Characterization and Evaluation of Materials; Biomaterials; Nanotechnology; Imaging / Radiology